Impact of Health Systems on the Implementation of Intermittent Preventive Treatment for Malaria in Pregnancy in Sub-Saharan Africa: A Narrative Synthesis - Atinuke O. Olaleye; Oladapo Walker (Tropical Medicine and Infectious Disease, 2020)
Malaria in pregnancy is a public health challenge with serious negative maternal and newborn consequences. Intermittent preventive treatment (IPTp) with sulphadoxine-pyrimethamine is recommended for the control of malaria during pregnancy within endemic areas, but coverage for the recommended ≥3 doses IPTp regimen has remained suboptimal. We searched PubMed, Cochrane library, and HINARI database from 1 January 2010 to 23 May 2020, for studies investigating the effect of the health system on IPTp implementation. Data extraction was independently performed by two investigators and evaluated for quality and content. Health system barriers and facilitators were explored using thematic analysis and narrative synthesis. Thirty-four out of 1032 screened articles were included. Key health system issues affecting the provision and uptake of IPTp were the ambiguity of policy and guidelines for IPTp administration, human resource shortages, drug stock-outs, conflicting policy implementation on free IPTp provision, hidden costs, unclear data recording and reporting guidelines, and poor quality of care. Factors affecting the supply and demand for IPTp services involve all pillars of the health system across different countries. The success of health programs such as IPTp will thus depend on how well the different pillars of the health system are articulated towards the success of each program.